The mitochondrial trifunctional protein: centre of a β-oxidation metabolon?. (February 2000) - Eaton, S.; Bursby, T.; Middleton, B.; Pourfarzam, M.; Mills, K.; Johnson, A. W.; Bartlecc, K.
Abstract : The trifunctional enzyme comprises three consecutive steps in the mitochondrial β-oxidation of long-chain acyl-CoA esters: 2-enoyl-CoA hydratase, 3-hydroxyacyl-CoA dehydrogenase and 3-ketoacyl-CoA thiolase. Deficiencies in either 3-hydroxyacyl-CoA dehydrogenase activity, or all three activities, are important causes of human disease. The dehydrogenase and thiolase have a requirement for NAD + and CoA respectively, whose levels are conserved within the mitochondrion and thus provide possible means for control and regulation of β-oxidation. Using analysis of the intact CoA ester intermediates produced by the complex, we have examined the sensitivity of the complex to NAD + /NADH and acetyl-CoA. We consider the evidence for channelling within the trifunctional protein and propose a model for a β-oxidation 'metabolon'.